An Unexpected Crisis? Looking at Pricing Effectiveness of Heterogeneous Banks. (23rd March 2017) - Vacca, Valerio
Abstract : Credit quality of loans to Italian firms dramatically worsened during the cyclical downturn of 2008–09, compared with the previous period of growth (2006–07). This paper shows that, if credit quality transition matrices (i.e. the change in the actual firms' riskiness, gauged ex post ) are mapped to interest rates (i.e. the conditions applied ex ante to the credit), banks appear to have been able at calibrating required risk premiums to actual firms' idiosyncratic risk, both during expansion and recession. However, the uncertainty generated by the crisis emphasized the unexpected component of credit worsening, thus making evident flaws in pricing effectiveness. Moreover, banks' organizational features did matter in driving the pricing effectiveness: the main finding is that larger banking groups were more affected than smaller ones by the sudden deterioration of credit quality, which was poorly reflected in their risk pricing on the eve of the crisis. The bank‐size effect can be tackled through an efficient use of hard or soft information: both the banks using quantitative credit rating models and highly decentralized banks showed an above‐average ability in calibrating rates to upcoming risk, suggesting that a clear‐cut adoption of a consistent lending technique outperforms more ambiguous strategies; banks with a strong relationship with borrowers smoothed the risk–price curve in normal times.